Differences across Countries and Time in Household Expenditure Patterns: Implications for the Estimation of Equivalence Scales - Angela Daley; Thesia Garner; Shelley Phipps; Eva Sierminska (Institute of Labor Economics (IZA), 2020)
When comparing economic well-being using income or expenditures, an equivalence scale is often used to adjust for differences in characteristics that affect needs. For example, a family of two is assumed to need more income than a single person, but not twice as much due to the economies of scale in consumption. In this study, we ask whether it is appropriate to use a common equivalence scale when comparing economic well-being across countries and/or time if consumption expenditure patterns differ? Based on an Engel methodology, we estimate equivalence scales for a diverse set of countries (Canada, France, Israel, Poland, South Africa, Switzerland, Taiwan, United States) in different time periods (1999-2012). We find considerable differences in economies of scale across countries, as well as increases over time. Notably, we find that economies of scale are larger than those implied by the widely accepted 'square root of household size' equivalence scale. Our results indicate that using a common equivalence scale to compare economic well-being across countries and/or time is misleading. Specifically, if economies of scale are understated (as is the case when using the 'square root of household size'), the relative poverty experienced by larger versus smaller families is being overstated.
Keywords: I3; D1; 330; economic well-being; Engel; necessities; equivalence scale; economies of scale; poverty